Benchmark study on glyphosate‐resistant cropping systems in the United States. Part 7: Effects of weed management strategy (grower practices versus academic recommendations) on the weed soil seedbank over 6 years. Issue 4 (15th June 2015) - Gibson, David J; Young, Bryan G; Owen, Micheal DK; Gage, Karla L; Matthews, Joseph L; Jordan, David L; Shaw, David R; Weller, Stephen C; Wilson, Robert G
Abstract: BACKGROUND: Shifts in weed species composition and richness resulting from near‐exclusive reliance on herbicides in glyphosate‐resistant (GR) cropping systems has necessitated the implementation of alternative weed management tactics to reduce selection pressures of herbicides. We contrasted the response of the weed soil seedbank to effects of weed management strategy, comparing grower practices with academic recommendations for best management practices (BMPs) over 6 years and across five weed hardiness zones in the US Midwest at sites subject to GR cropping systems. RESULTS: Total weed population density and species richness varied according to cropping system, location and prior year's crop, but less so to weed management strategy. The seedbank population density for 11 of the 14 most frequent weed species was affected by weed management strategy either alone or in an interaction with hardiness zone or year, or both. In only 29% of comparisons was weed population density lower following academic recommendations, and this depended upon prior crop and cropping system. The population density of high‐risk weed species was reduced by academic recommendations, but only in two of six years and under continuous GR maize. Overall, the weed population density was decreasing in field halves subject to the BMPs in the academic recommendations relative to grower practices. CONCLUSION: The soil seedbank is slow to respond to academic recommendations to mitigate glyphosate‐resistant weeds, but represents a biological legacy that growers need to keep in mind even when management practices reduce emerged field weed population densities. © 2015 Society of Chemical Industry